Етапи становлення комп’ютерної термінології на тлі розвитку інформаційних технологій в Україні - Ментинська, І. (Львівський національний університет ім. І. Франка, 2023)
The article traces the formation of computer terminology against the background of the development of information technologies in Ukraine. Important stages of establishment of this field of knowledge are high lighted. Special attention is paid to the main lexicographical works, which became basic in the formation of the term system. The relevance of scientific research is determined by the need for a scientific description of the his tory of the development of Ukrainian computer terminology, as well as the need to determine the periodization of the formation of Ukrainian computer terminology. To realize the goal, the following tasks were completed1) describe the development of IT technologies in Ukraine; 2) the main stages of the adoption of computer terms against the background of the development of the computer industry are revealed; 3) lexicographical works that became basic in the formation of the computer sphere were carefully considered; 4) the peculiarities of the func tioning of computer terms at each stage of development are established. The study of the history of the formation and development of industry terminology against the background of the development of information technologies in Ukraine makes it possible to determine the main regu larities of the formation of the term system, to forecast the trends of its development using logical and linguistic ordering and a well-founded lexicographic description. The development and systematization of computer terminology are complex and ambiguous. We single out five important stages of the establishment of the computer industry against the background of the develop ment of IT technologies in Ukraine: the 1st stage (beginning of the 20th century); 2nd (1941–1959); 3rd (1960-1989); 4th (1990–2000); 5th (early 2000 – until today). We trace that the emergence of information technologies in Ukraine dates back to 1914, however, due to intralingual and extra lingual factors, Ukrainian computer termi nology developed sluggishly during the first and second periods. However, the fourth and fifth periods are characterized by rapid development and consistent systemati zation of the branch terminology. The main lexicographic works, which can be called basic in the formation of computer terminology, were the dictionaries of the 20 and 30 years of the 20th century. An important basis for establishing and codifying computer term units is the “Cybernetics Encyclopedia”, and at the current stage of development, online dictionaries of they IT. In the future, it would be worth investigating the stages of develop ment of thermographic processing in the computer industry in Ukraine and abroad.
Keywords: terminology; term; computer technologies; lexicographic works.